SK Sri Iman educational visit - Siti Muslihah, Isnain; Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
27 June 2012. Centre for Modern Languages and Human Sciences (CMLHS) received a visit from Sekolah Kebangsaan Sri Iman, Terengganu.